Supporting Medical Student Mental Health during COVID-19: Strategies Implemented for an Accelerated Curriculum Medical Campus. (May 2021) - Chandratre, Sonal; Knight, Christopher; Dodson, Lisa
Medical student education has not been immune to life altering changes of the global Coronavirus disease 2019 (COVID-19) pandemic. Pre-pandemic anxiety and mental health concerns were already a significant problem in the world of medical student education. Educators are reformulating strategies to address the increased demand for mental health services and wellness during COVID-19. Adaptations include increased and varied internal and student focused communication, as well as new support structures built around student connection and coaching, mental illness, and general wellness. Additional alterations to student support include expanded mental health counseling and also incorporating novel wellness events in an effort to support thriving during COVID-19.